Significant reduction of patellar height affected lower clinical outcomes and knee flexion over five- year follow- up after total knee arthroplasty. (2021) - Suthar, A.; Yukata, K.; Azuma, Y.; Suetomi, Y.; Yamazaki, K.; Seki, K.; Sakai, T.; Fujii, H.
No abstract available